Pre‐ and postcontrast T1 and T2 mapping of patellar cartilage in young adults with recurrent patellar dislocation. Issue 5 (24th November 2014) - Bengtsson Moström, Eva; Lammentausta, Eveliina; Finnbogason, Thröstur; Weidenhielm, Lars; Janarv, Per‐Mats; Tiderius, Carl Johan
<x xml:space="preserve">Abstract</x> Purpose To examine the cartilage quality in young adults with recurrent patellar dislocation in childhood using different magnetic resonance imaging parameters. Methods Sixteen young adults with unilateral recurrent patellar dislocation were investigated ≥5 y (mean, 8.5 y) after the first dislocation. Pre‐ and postcontrast T1 and precontrast T2 relaxation times were analyzed in four superficial and four deep patellar cartilage regions of both knees. Two hours after intravenous injection of 0.2 mM/kg Gd‐DTPA2−, postcontrast T1 [T1(Gd)] and ΔR1 [1/T1 (precontrast) − 1/T1 (postcontrast)] were analyzed in the regions. Muscle performance and patient‐reported outcome were evaluated. Results When comparing the injured side with the noninjured side, differences were seen in the superficial half but not the deep half of the cartilage. T1(Gd) was shorter in the central part, whereas T2 was shorter in the periphery of the patellar cartilage (P < 0.05). ΔR1 demonstrated similar differences between healthy and diseased cartilage as T1(Gd) alone. The knee function was not correlated to the degenerative changes. Conclusion The short T1(Gd) centrally indicates degenerative cartilage changes consistent with loss of glycosaminoglycans. Precontrast and ΔR1 calculations may be excluded in clinical dGEMRIC, which simplifies the procedure. A decrease in T2 may be a very early sign of joint pathology but warrants further investigation. Magn Reson Med 74:1363–1369, 2015. © 2014 Wiley Periodicals, Inc.